Normalgewebe: Strahlenempfindlichkeit, Toxizität, Konsequenzen für die Planung = Normal tissue : radiosensitivity, toxicity, consequences for planning - Rühle, Alexander; Huber, Peter E. (Der Radiologe, 2018)
Along with chemotherapy, surgery and immunotherapy, radiotherapy is a mainstay of cancer treatment. Considering the improving survival rates for various malignancies during the past decades, the importance of radiation-induced late normal tissue response is increasing. Quality of life is becoming an important issue in modern cancer treatment and is correlated with acute and late normal tissue response after radiotherapy. A profound understanding of radiation-induced normal tissue response is necessary to sufficiently diagnose and treat radiation-induced side effects and thereby increase the patients’ quality of life. Here, the various normal tissue responses in consideration of the radiation biology are specified and prospective options to attenuate radiation-induced side effects are discussed.
Gesehen am 25.04.2019